2017
DOI: 10.1386/rjao.15.2.243_1
|View full text |Cite
|
Sign up to set email alerts
|

All the lonely people, where do they all belong: Community radio and social connection

Abstract: The Community Broadcasting Association of Australia (CBAA) asserts that community radio should promote a culturally diverse society by representing those sections of the community much less visible in the mainstream media. This echoes the Australian Federal Government’s vision of social inclusion/cohesion in a society in which all Australians are valued and are able to participate fully. There are those, however, who are marginalised by mainstream culture and can find themselves alienated as a result of, for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Many listeners become producers and are in fact encouraged to do so. This interchange of roles is a defining feature of community radio and is an important distinction from mainstream radio (Meadows et al, 2007;Milan, 2008;Oliveira, 2013;Order, 2017;Purkarthofer et al, 2008).…”
Section: Creating a Sense Of Communitymentioning
confidence: 99%
See 3 more Smart Citations
“…Many listeners become producers and are in fact encouraged to do so. This interchange of roles is a defining feature of community radio and is an important distinction from mainstream radio (Meadows et al, 2007;Milan, 2008;Oliveira, 2013;Order, 2017;Purkarthofer et al, 2008).…”
Section: Creating a Sense Of Communitymentioning
confidence: 99%
“…This function also extends from production to the audience; listeners, tuning in to hear about various social issues, in turn often become more active within the community (Milan, 2008). Community radio also disseminates content which builds community; Order (2017) found that specialized cultural programming can engage both older and younger generations in discussion, in an attempt to combat a feeling of alienation often experienced by first generation migrant youth towards their parents' home culture.…”
Section: Creating a Sense Of Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…Research on community radio suggests that it can enhance well-being (Meadows et al, 2007;Oliveira, 2013;Order, 2017). For instance, older adults gain a sense of purpose and identity by volunteering at radio stations (Order and O'Mahony, 2017).…”
Section: Introductionmentioning
confidence: 99%